The Effect of Compensation, Work Discipline, and Work Motivation on the Performance of Non-Civil Servant Employees at the Secretariat Office of the Regional House of Representatives (DPRD) of Tanggamus Regency - Eliyanti, Eliyanti; Hasbullah, Hasbullah; Kumalasari, Nety (LPPPIPublishing, 2026)
The purpose of this study is to examine the effect of compensation, work discipline, and work motivation on employee performance both simultaneously and partially. This research employs a quantitative approach with an associative design. The population consists of 137 non-civil servant employees, with a sample of 35 respondents selected using non-probability sampling techniques. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS version 23. The results show that compensation, work discipline, and work motivation simultaneously have a positive and significant effect on employee performance, as indicated by an F-value of 10.342, which is greater than the F-table value of 2.910, and a significant level of 0.000, which is less than 0.05. Partially, compensation has a positive and significant effect on performance, with a t-value of 3.528 greater than the t-table value of 2.0369 and a significance level of 0.037. Work discipline also shows a positive and significant effect, with a t-value of 3.716 and a significance level of 0.001. Furthermore, work motivation has a positive and significant effect on performance, with a t-value of 3.435 and a significance level of 0.006. Therefore, improving employee performance can be achieved through appropriate compensation, effective implementation of work discipline, and continuous enhancement of work motivation.